The expressive importance of humanization in labor (Research, Society and Development, 2021)
Introduction: The term humanize refers us to care that values the quality of care from a technical point of view, associated with respect for the patient's rights, their subjectivity and cultural references, as well as the valuation of the professional and of intra- and inter-team dialogue. The moment of delivery, involves many biological, social and psychological issues for the woman and her baby, the doctor needs to understand the sensitivity that surrounds the pregnant woman at that time. Methodology: It is a narrative review of the literature The data used in this research are characterized as secondary, that is, based on data already treated, taken from books and works to show the concept, treatment and its particularities.Results: The need of trained and sensitized health professionals in prenatal care and in the delivery period is of fundamental importance, since this is a painful and uncomfortable moment for women. Therefore, making it less traumatic should be one of the goals of the entire care team. Conclusion: After reading and analyzing the articles, it was found that for nursing to contribute to improving the quality of women's health care, it is essential that the interventions carried out can guarantee physical and mental health, respect and dignity, offering humanized care throughout the pregnancy and childbirth cycle, understanding pregnancy and childbirth as physiological events, developing the role of the woman in childbirth, where she actively participates in decisions being able to express their wishes and choices, deciding together with the team the best method to be adopted.